Reverse logistics : emerging trends, opportunites and challenges : considerations in establishment of a household waste medicine reverse logistics system in Singapore - Ma, Ruiyuan (2017)
Disposal of unwanted pharmaceuticals in households as domestic wastes or sewage is harmful to the environment and increases the risk of misuse, in addition to causing economic value lost. Unwanted medicine reverse logistics (RL) systems are established in many countries to minimize the negative impacts. This paper pioneers in proposing a household waste medicine RL system in Singapore by integration of best practices from pharmaceutical RL schemes overseas and electronic waste recycling programs in Singapore. Detailed comparison of unwanted medicine RL systems in Italy, France, the UK and the US reveals major considerations in establishment of a pharmaceutical RL system, for example, range of wastes covered, system implementation and coordination, and drivers. Investigations on electronic waste recycling programs in Singapore demonstrate local resources available for a voluntary waste collection network, with which its publicity and sustainability can be generated. This study partially closes a gap by proposing a theoretical RL framework which is not evaluated by professional stakeholders. The feasibility and cost efficiency of the recommendations need to be tested in further studies.